2010
DOI: 10.1111/j.1574-6941.2010.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of low-molecular-weight alkanes under mesophilic, sulfate-reducing conditions: metabolic intermediates and community patterns

Abstract: We evaluated the ability of the native microbiota in a low-temperature, sulfidic natural hydrocarbon seep (Zodletone) to metabolize short-chain hydrocarbons. n-Propane and n-pentane were metabolized under sulfate-reducing conditions in initial enrichments and in sediment-free subcultures. Carbon isotope analysis of residual propane in active enrichments showed that propane became enriched in (13)C by 6.7 (+/-2.0) per thousand, indicating a biological mechanism for propane loss. The detection of n-propylsuccini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 64 publications
(97 reference statements)
4
63
0
Order By: Relevance
“…The oxidation of non-methane alkanes with sulfate has recently been reported to occur across a range of temperatures in diverse marine and terrestrial seeps or vents (e.g. Joye et al, 2004;Kniemeyer et al, 2007;Orcutt et al, 2010;Savage et al, 2010;Quistad and Valentine, 2011;Jaekel et al, 2012;Adams et al, 2013;Bose et al, 2013). Measured rates of alkane degradation and SR closely followed stoichiometric predictions that assume complete oxidation of alkanes to CO 2 (e.g.…”
Section: Introductionmentioning
confidence: 65%
“…The oxidation of non-methane alkanes with sulfate has recently been reported to occur across a range of temperatures in diverse marine and terrestrial seeps or vents (e.g. Joye et al, 2004;Kniemeyer et al, 2007;Orcutt et al, 2010;Savage et al, 2010;Quistad and Valentine, 2011;Jaekel et al, 2012;Adams et al, 2013;Bose et al, 2013). Measured rates of alkane degradation and SR closely followed stoichiometric predictions that assume complete oxidation of alkanes to CO 2 (e.g.…”
Section: Introductionmentioning
confidence: 65%
“…Quantitative growth experiments showed that the enrichment cultures degraded propane or butane completely to CO 2 , with stoichiometric reduction of sulfate to sulfide, as described before (Kniemeyer et al, 2007;Savage et al, 2010). The enrichment cultures were tested for their ability to degrade methane, the dominant hydrocarbon at gas seeps and other alkanes found in relatively high concentrations in such environments, for example, ethane, isobutane and pentane.…”
Section: Growth Tests With Other Hydrocarbonsmentioning
confidence: 96%
“…In addition, oxidation of propane under anoxic conditions has been determined in sediments collected from marine gas seeps (Quistad and Valentine, 2011). Anaerobic degradation of shortchain alkanes was demonstrated recently with a pure culture of a marine sulfate-reducing bacterium strain BuS5, isolated from Guaymas Basin hydrothermal vent sediments (Kniemeyer et al, 2007), and with several enrichment cultures obtained from sediments around marine and terrestrial hydrocarbon seeps (Kniemeyer et al, 2007;Savage et al, 2010). Strain BuS5 can degrade both propane and butane and is phylogenetically affiliated with the Desulfosarcina-Desulfococcus cluster of the Deltaproteobacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this reductive dechlorination process, RSCs served as nucleophilic reductants and/ or electron donor, and ultimately transformed into oxidized sulfur compounds (OSCs) (Zheng et al, 2006). Besides the level of sulfate, the amended organic material which serves as both electron donor and carbon source (Savage et al, 2010) was another limiting factor for the generation of RSCs. SRB can utilize an impressive array of organic matter to support their metabolic activity (Zhang and Young, 1997;Aeckersberg et al,1998).…”
Section: Dechlorination Mechanism Of Pp 0 -Ddts By Clostridium Sp Bmentioning
confidence: 99%